Method for improving stability of quantum dots
Through high-temperature thermal injection of quantum dots after synthesis and surface ligand exchange, combined with high-temperature spraying and ALD coating technology, a stable quantum dot film is formed, which solves the problem of instability of the optical performance of quantum dots in harsh environments and improves its lifetime and stability in Micro-LED applications.
Patent Information
- Application Number
- CN202311372979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-20
AI Technical Summary
The optical performance of quantum dot materials in harsh environments of ultra-high light intensity, temperature and humidity is unstable, and in Micro-LED full-color applications, the lifespan of red and green quantum dots is a key issue.
The synthetic alloyed core-shell quantum dots are injected by high temperature heat and surface ligand exchange is performed to make them highly dissolved in the polar solvent DMF. Then, the solvent is removed by high-temperature spray method, the polymer is coated with quantum dots, and an Al2O3 layer is deposited outside the polymer layer by atomic layer deposition (ALD), and finally coated and photocured on the optically transparent substrate to form a stable quantum dot film.
It effectively improves the stability and lifetime of quantum dots, making them more applicable in commercial Mini-LED and Micro-LED scenarios, especially in high-light intensity and harsh environments, with the optical performance stable.
Smart Images

Figure CN119875614A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of optoelectronic display materials, and in particular, relates to a method for improving the stability of quantum dots. Background Art
[0002] Quantum dots are an excellent semiconductor light-emitting material with unique optoelectronic properties and broad application prospects. According to their physical properties, the application of quantum dots in display is mainly divided into two ways: electroluminescence and photoluminescence. At present, quantum dot light-emitting diodes (AM-QLED) based on electroluminescence are in the research and development stage and are close to commercialization. Applications using photoluminescence mainly include quantum dot light conversion film / quantum dot diffusion plate and quantum dot color filter. The former has been widely used in products such as televisions. By adding a layer of quantum dot light conversion film / quantum dot diffusion plate to the blue light backlight, a white light backlight is obtained, and then combined with the color filter film inside the liquid crystal display panel, full-color display is achieved, and its color gamut, color purity, and resolution are significantly enhanced.
[0003] Take Micro-LED, a hot micro-display technology in recent years, as an example. Compared with LCD, OLED and other display technologies, Micro-LED has greater advantages in brightness, resolution, contrast, energy consumption, service life, response speed, thermal stability and other aspects. These advantages make Micro-LED applicable to applications such as AR / VR and wearable display that have high requirements for power consumption, brightness, response speed, etc. The difficulty of full-colorization of Micro-LED is mainly reflected in the fact that to achieve full-colorization of Micro-LED, the traditional means require three colors of RGB LEDs. The driving voltage of each LED is different, which will increase the requirements for driving circuit design; secondly, the composition of the materials of RGB LEDs is different. Due to the differences in the aging attenuation curves of different materials, there is a greater possibility that the color accuracy of LEDs will fluctuate throughout the life cycle. Similarly, for the full-colorization of Micro-LED using quantum dot solutions, the life extension of red and green quantum dots is crucial, and it is also a promotion of high-end display technology. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a method for improving the stability of quantum dots, wherein the method synthesizes alloyed core-shell quantum dots by high-temperature hot injection, and then performs surface ligand exchange to make them highly soluble in polar solvent DMF, and removes the solvent by high-temperature spraying, so that the polymer is coated with quantum dots, and further deposits a layer of Al2O3 with uniform thickness and controllable thickness on the outside of the polymer layer by atomic layer deposition (ALD) method, and further coats the quantum dots, and finally mixes the photosensitive resin, and coats and photocures the film on an optically transparent substrate, which solves the problem of unstable optical performance of quantum dot materials in harsh environments of ultra-high light intensity, temperature and humidity. And through the effective exchange of surface ligands, the optical properties of quantum dots are not affected, and their solubility in the DMF system is increased. The polymer coating layer and the ALD coating layer protect the quantum dots well from the influence of oxygen and water vapor. It makes it more possible to use quantum dots in commercial MiniLED scenes and Micro LED scenes, and opens up a new technical route for improving the life of quantum dots and scene applications.
[0005] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:
[0006] In one aspect, the present application provides a method for improving the stability of quantum dots, comprising the following steps:
[0007] (1) Obtaining core-shell quantum dot materials;
[0008] (2) dissolving the core-shell quantum dot material, evacuating until there are no bubbles, heating, adding a quantum dot exchange ligand, cooling to room temperature, adding a precipitant, and centrifuging to obtain a polar quantum dot material;
[0009] (3) heating and dissolving the mixture containing the polar quantum dot material and the polymer until a uniform and stable quantum dot polymer precursor gel is formed;
[0010] (4) atomizing and instantaneously drying the quantum dot polymer precursor colloid in sequence to obtain quantum dot polymer microspheres;
[0011] (5) Performing Al2O3 atomic layer deposition on the quantum dot polymer microspheres to obtain coated quantum dot polymer microspheres.
[0012] Optionally, in step (1), the core-shell quantum dot material includes at least one of CdSe@ZnS, CdSe@CdS, ZnSe@ZnS, and ZnSe@CdS.
[0013] Optionally, in step (1), the method for obtaining the core-shell quantum dot material includes a high-temperature hot injection synthesis method.
[0014] Optionally, in step (2), the solvent used for dissolving is a polar solvent.
[0015] Optionally, the polar solvent includes N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).
[0016] Optionally, in step (2), the heating is carried out under an inert gas atmosphere.
[0017] Optionally, in step (2), the heating is increased to 100-350°C.
[0018] Preferably, in step (2), the temperature is increased to 320°C.
[0019] Optionally, in step (2), the quantum dot exchange ligand includes at least one of 6-mercapto-1-hexanol, 2-mercapto-3-butanol, 3-mercapto-1-propanol, and 2,3-dimercaptopropanol.
[0020] Optionally, in step (2), the ratio of the core-shell quantum dot material to the quantum dot exchange ligand is 45-55 mg: 1-3 mL.
[0021] Optionally, in step (2), the cooling is carried out under a nitrogen atmosphere.
[0022] Optionally, in step (2), the precipitant comprises toluene.
[0023] Optionally, in step (2), the ratio of the core-shell quantum dot material to the precipitant is 45-55 mg: 5-13 mL.
[0024] Optionally, in step (2), the centrifugal speed is 6000-8000 rpm;
[0025] The centrifugation time is 1 to 5 minutes.
[0026] Optionally, in step (2), the centrifugal rotation speed is independently selected from any value among 6000 rpm, 6500 rpm, 7000 rpm, 7500 rpm, 8000 rpm or any range between two values.
[0027] Optionally, the centrifugation time is independently selected from any value among 1 min, 2 min, 3 min, 4 min, 5 min, or any range between the two.
[0028] Optionally, in step (3), the polymer includes at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene-methyl methacrylate copolymer (MS), polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), polyacrylonitrile (PAN), and acrylonitrile-styrene resin (AS).
[0029] Optionally, in step (3), the mixing mass ratio of the polar quantum dot material to the polymer is 1-3:20-35.
[0030] Optionally, in step (3), the solvent used for the heating and dissolving is a polar solvent.
[0031] Optionally, the polar solvent includes N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).
[0032] Optionally, in step (3), the temperature of heating and dissolving is 40 to 60°C.
[0033] Optionally, in step (4), the atomization temperature is 60 to 100° C.;
[0034] The atomizing gas pressure is 70-100 MPa;
[0035] The frequency of the atomizing fan is 20-50 Hz.
[0036] Optionally, in step (4), the atomization temperature is independently selected from any value among 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any range between two thereof.
[0037] Optionally, the atomization gas pressure is independently selected from any value among 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa, 100 MPa, or any range value therebetween.
[0038] Optionally, the atomizing fan frequency is independently selected from any value among 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz or any range value therebetween.
[0039] Optionally, in step (4), the instantaneous drying temperature is 100-150°C.
[0040] Optionally, in step (5), the thickness of the Al2O3 atomic layer deposition is 10 to 100 nm.
[0041] Optionally, in step (5), the thickness of the Al2O3 atomic layer deposition is independently selected from any value among 10nm, 20nm, 30nm, 50nm, 70nm, 100nm or any range between two values.
[0042] Optionally, the method further comprises step (6): coating and photocuring a mixed glue solution containing the coated quantum dot polymer microspheres, prepolymer, monomer and photoinitiator in sequence to obtain a quantum dot film.
[0043] Optionally, the prepolymer includes at least one of aliphatic polyurethane acrylate, aliphatic polyurethane hexaacrylate, tin-free aliphatic polyurethane diacrylate, aromatic polyurethane acrylate, aromatic polyurethane hexaacrylate, fluorine-modified polyurethane acrylate, silicone-modified polyurethane acrylate, 2-hydroxy-3-phenoxypropyl acrylate, epoxy acrylate, modified epoxy acrylate, epoxy methacrylate, fatty acid-modified epoxy acrylate, modified bisphenol A epoxy acrylate, phenolic epoxy acrylate, epoxy soybean oil acrylate, fatty acid-modified polyester hexaacrylate, fatty acid-modified polyester acrylate, chlorinated polyester resin, modified polyester acrylate, amine-modified polyester acrylate, hyperbranched polyester acrylate, rosin-modified polyester acrylate, tertiary amine acrylate, hot-melt pure acrylate resin, pure acrylic resin, organic-inorganic hybrid acrylate oligomer, melamine acrylate, silicon-modified polyurethane acrylate, and polycaprolactone acrylate.
[0044] Optionally, the monomer includes at least one of 4-tert-butylcyclohexyl acrylate, methacrylate ethylene urea ethoxylate, m-phenoxybenzyl acrylate, dicyclopentenyl acrylate, dicyclopentenyl ethoxylated acrylate, ethoxylated phenoxy acrylate, 3,3,5-trimethylcyclohexyl acrylate, o-phenylphenoxyethyl acrylate, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, ethoxyethoxyethyl acrylate, 3-hydroxy-2,2-dimethylpropyl-3-hydroxy-2,2-dimethylpropyl acrylate, tricyclodecane dimethanol diacrylate, dioxanediol diacrylate, polypropylene glycol (700) diacrylate, 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate.
[0045] Optionally, the photoinitiator includes at least one of 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, isopropylthioxanthone (2,4 isomer mixture), 4-(N,N-dimethylamino)ethyl benzoate, 4-(N,N-dimethyl)benzoic acid isooctyl ester, 2-isopropylthioxanthone, 2-benzyl-2-(dimethylamino)-4-morpholine, 4-phenylxylene ketone, and methyl o-benzoylbenzoate.
[0046] Optionally, the mixing mass ratio of the finished quantum dot polymer microspheres, prepolymer, monomer and photoinitiator is 1-3:1-4:2-5:0.1-0.3.
[0047] Optionally, the coating is to coat the mixed glue solution between the PET surfaces of the diffusion barrier film, with the diffusion barrier film on both the top and the bottom.
[0048] Optionally, the coating has a thickness of 20 to 60 μm.
[0049] Optionally, the coating thickness is independently selected from any value among 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, or any range therebetween.
[0050] Optionally, the photocuring is performed using an ultraviolet lamp.
[0051] Optionally, the wavelength of the ultraviolet lamp is 365nm.
[0052] Optionally, the energy of the light curing is 500 to 2500 mj / cm 2 .
[0053] Optionally, the energy of the photocuring is independently selected from 500 mj / cm 2 、750mj / cm 2 、1000mj / cm 2 、1250mj / cm 2 、1500mj / cm 2 、1750mj / cm 2 、2000mj / cm 2 、2250mj / cm 2 、2500mj / cm 2 Any value in between or any range of values between them.
[0054] Compared with the prior art, this application has the following beneficial effects:
[0055] (1) In the method of the present application, core-shell quantum dots are first synthesized by high-temperature hot injection. The quantum dots have covalent bond properties and more stable physical and chemical properties. In addition, the generated shell plays a good protective role for the internal luminescent structure and defect passivation.
[0056] (2) The present application performs surface ligand exchange on quantum dots synthesized by high temperature hot injection and dissolved in toluene non-polar solvent, and modifies them into alcohol-soluble quantum dots, which can be highly soluble in DMF polar solvent and well mixed with polymer for spray coating.
[0057] (3) The present application utilizes an atomic layer deposition (ALD) coating method to deposit oxide on the surface of quantum dot polymer microspheres. The thickness of the surface deposition layer is controllable, which achieves a good single particle coating effect and can be applied to a variety of scenarios, avoiding the use of expensive water and oxygen barrier films. The thickness of the product design can also be thinned.
[0058] (4) The present application changes the solubility through surface ligand exchange and performs subsequent polymer coating and ALD coating, which can effectively protect quantum dots from external light, heat, humidity, oxygen, and water vapor stimulation, and ensure the long-term processing and service life of quantum dots, making it more likely to be used in commercial Mini-LED scenarios and Micro-LED scenarios. In particular, the high light intensity required by micro-displays puts more stringent requirements on the photostability of quantum dots; the method of coating dispersion and ALD deposition can greatly improve the dispersion of nano quantum dots, which is beneficial to their structural design at high concentrations. The quantum dots will not easily agglomerate, avoiding the degradation of optical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 Schematic diagram of the method for improving the stability of quantum dots in this application. DETAILED DESCRIPTION
[0061] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0062] Unless otherwise specified, the raw materials in the comparative examples and embodiments of the present application were purchased from commercial sources and used directly without any special treatment.
[0063] Unless otherwise specified, the analysis methods in the comparative examples and embodiments all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0064] The schematic diagram of the method for improving the stability of quantum dots in this application is as follows Figure 1 As shown, A1 represents the synthesis of quantum dots by high-temperature hot injection, A2 represents the ligand exchange on the surface of quantum dots, A3 represents the dispersion of modified quantum dots into DMF+polymer solution, A4 represents the formation of polymer microsphere shells by high-temperature spraying, A5 represents the ALD coating of quantum dot polymer microspheres, and A6 represents the preparation of films for aging tests.
[0065] Comparative Example 1
[0066] Preparation of CdSe@ZnS (without polymer coating, without ALD coating):
[0067] First weigh 40mL of TOP precursor, stir with 0.53g of selenium powder and 2.135g of sulfur powder until it is clear, and set aside. The main reaction system A, that is, 12mmol of zinc acetate, 1.2mmol of cadmium oxide, 18mL of oleic acid and 60mL of octadecene in a 250mL three-necked flask, is vacuum ventilated 3 times at 120℃ until there are no bubbles, then heated to 320℃ under nitrogen protection, at which time the solution is a light yellow transparent solution, and the TOP precursor solution is quickly injected, and the solution changes from light yellow to reddish brown. The coating material system B, that is, 4.130g of zinc acetate, 45mL of DDT, and 45mL of ODE in a 250mL three-necked flask, is vacuum ventilated three times at 100℃ until there are no bubbles, and heated to 120℃ for use. After the main system A reacts for a period of time, the material in the main system A is coated with system B, the peristaltic pump is adjusted to the slowest speed, 2mL of Zn(DDT) is injected, and the injection plus reaction time is 7min in total before the next injection coating. According to the above method, the core-shell structure quantum dots are dispersed in the organic solvent, the three-necked bottle containing the quantum dot solution is placed on the magnetic stirrer, and the precipitant is added in proportion, the volume ratio of methanol: acetone = 2: 1, with the addition of the precipitant, the quantum dot solution gradually changes from clear to turbid solution, and the high-speed centrifuge is used for centrifugation at a speed of 7000 revolutions per minute for 3min, the quantum dots are precipitated, the precipitate is taken out and a small amount of toluene solvent is added to dissolve the quantum dots, and the above steps are repeated under stirring to add the precipitant for secondary cleaning. Toluene was added to the precipitate after centrifugation to dissolve it, and then a precipitant was added under stirring in a volume ratio of acetone: acetic acid = 2:1. The mixture was also centrifuged in a high-speed centrifuge at 7000 rpm for 3 min. The precipitate was washed twice and dried in a vacuum drying oven to obtain a powder quantum dot material. After it was completely dried, it was ground in a mortar and set aside to obtain a stable CdSe@ZnS quantum dot material, recorded as sample 1.
[0068] Comparative Example 2
[0069] Preparation of CdSe@ZnS (PMMA polymer coating, no ALD coating):
[0070] On the basis of sample 1, surface ligand exchange and high-temperature spraying were performed to obtain sample 2. The specific steps are as follows: 50 mg of the CdSe@ZnS quantum dot powder obtained in comparative example 1 was dispersed in 5 mL of DMF solvent, and a stirring bar was used to make it evenly dispersed. Vacuum ventilation was performed 3 times until there were no bubbles. The reaction system was heated to 130 ° C under nitrogen protection, and 2 mL of 6-mercapto-1-hexanol was quickly injected. After a moment of reaction, the solution changed from turbid to a clear and transparent solution. Under nitrogen protection, it was naturally cooled to room temperature, and the precipitant toluene was added to the original reaction system solution. As the amount of toluene increased, it was seen that the clear solution gradually became turbid, indicating that the dispersibility of the quantum dots in the solution was weakened and gradually precipitated. In a high-speed centrifuge, a speed of 7000 revolutions per minute was used for centrifugation for 3 minutes to precipitate the quantum dots, remove the precipitate and place it in a fume hood to dry, and grind it in a mortar after it was completely dried, and seal it for storage. Repeated preparation and modification of large quantities of quantum dots were carried out according to the same ratio. Then, 5g of surface-modified quantum dots and 20g of PMMA polymer were weighed and put into 100g of polar solvent DMF, and heated at 50°C for a long time to dissolve to form a uniform and stable liquid precursor gel. The prepared quantum dot polymer precursor solution was transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and was atomized into droplets using high-pressure nitrogen, and most of the polar solvent was instantly removed by a high-temperature thermal field (100°C). The whole process experienced a process of droplet atomization and instant drying in a high-temperature thermal field. The equipment pressure was controlled to 75MPa and the fan frequency was 30Hz. The quantum dot microsphere polymer powder was collected by the cyclone collector of the spray equipment, and the obtained quantum dot polymer powder was recorded as sample 2.
[0071] Example 1
[0072] Preparation of CdSe@ZnS (PMMA polymer coating, ALD coating):
[0073] On the basis of sample 1, surface ligand exchange, high temperature spraying and ALD coating were performed to obtain sample 3. The specific steps are as follows: 50 mg of the CdSe@ZnS quantum dot powder obtained in comparative example 1 was dispersed in 5 mL of DMF solvent, and a stirring bar was used to make it evenly dispersed. The vacuum was ventilated 3 times until there were no bubbles. The reaction system was heated to 130 ° C under nitrogen protection, and 2 mL of 6-mercapto-1-hexanol was quickly injected. The solution changed from turbid to clear and transparent solution after a moment of reaction. It was naturally cooled to room temperature under nitrogen protection, and the precipitant toluene was added to the original reaction system solution. As the toluene increased, it can be seen that the clear solution gradually became turbid, indicating that the dispersibility of the quantum dots in the solution was weakened and gradually precipitated. The high-speed centrifuge was centrifuged at a speed of 7000 revolutions per minute for 3 minutes to precipitate the quantum dots, remove the precipitate and place it in a fume hood to dry, and grind it in a mortar after it is completely dried, and seal it for storage. Repeat the preparation and modification of large quantities of quantum dots according to the same ratio. Then, 5g of surface-modified quantum dots and 20g of PMMA polymer were weighed and put into 100g of polar solvent DMF, and heated at 50℃ for a long time to dissolve to form a uniform and stable liquid precursor gel. The prepared quantum dot polymer precursor solution was transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and was atomized into droplets by high-pressure nitrogen, and most of the polar solvent was instantly removed by a high-temperature thermal field (100℃). The whole process experienced the process of droplets becoming smaller and atomized, and the high-temperature thermal field was instantly dried. The equipment pressure was controlled to 75MPa and the fan frequency was 30Hz, and the quantum dot microsphere polymer powder was collected by the cyclone collector of the spray equipment. By setting the ALD coating equipment parameters and controlling the thickness of the Al2O3 deposition layer to 20nm, the quantum dot polymer powder was ALD coated, and the obtained ALD coated quantum dot polymer powder was recorded as sample 3.
[0074] Example 2
[0075] Preparation of CdSe@ZnS (PVDF polymer coating, ALD coating):
[0076] On the basis of sample 1, surface ligand exchange, high temperature spraying and ALD coating were performed to obtain sample 4. The specific steps are as follows: 50 mg of the CdSe@ZnS quantum dot powder obtained in comparative example 1 was dispersed in 5 mL of DMF solvent, and a stirring bar was used to make it evenly dispersed. The vacuum was ventilated 3 times until there were no bubbles. The reaction system was heated to 130 ° C under nitrogen protection, and 2 mL of 6-mercapto-1-hexanol was quickly injected. The solution changed from turbid to clear and transparent solution after a moment of reaction. It was naturally cooled to room temperature under nitrogen protection, and the precipitant toluene was added to the original reaction system solution. As the toluene increased, it can be seen that the clear solution gradually became turbid, indicating that the dispersibility of the quantum dots in the solution was weakened and gradually precipitated. The high-speed centrifuge was centrifuged at a speed of 7000 revolutions per minute for 3 minutes to precipitate the quantum dots, remove the precipitate and place it in a fume hood to dry, and grind it in a mortar after it is completely dried, and seal it for storage. Repeat the preparation and modification of large quantities of quantum dots according to the same ratio. Then weigh 5g of the surface-modified quantum dots and 20g of PVDF polymer and put them into 100g of polar solvent DMF, and heat and dissolve them at 50℃ for a long time to form a uniform and stable liquid precursor gel. The prepared quantum dot polymer precursor solution is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets by high-pressure nitrogen, and is instantly removed by a high-temperature thermal field (100℃). The whole process undergoes a process of droplet atomization and instant drying in a high-temperature thermal field. The equipment pressure is controlled to 75MPa and the fan frequency is 30Hz, forming a quantum dot microsphere polymer powder that is collected by the cyclone collector of the spray equipment. By setting the ALD coating equipment parameters and controlling the thickness of the Al2O3 deposition layer to 20nm, the quantum dot polymer powder is ALD coated, and the obtained ALD coated quantum dot polymer powder is recorded as sample 4.
[0077] Example 3
[0078] Preparation of CdSe@ZnS (EVOH polymer coating, ALD coating):
[0079] On the basis of sample 1, surface ligand exchange, high temperature spraying and ALD coating were performed to obtain sample 5. The specific steps are as follows: 50 mg of the CdSe@ZnS quantum dot powder obtained in comparative example 1 was dispersed in 5 mL of DMF solvent, and a stirring bar was used to make it evenly dispersed. The vacuum was ventilated 3 times until there were no bubbles. The reaction system was heated to 130 ° C under nitrogen protection, and 2 mL of 6-mercapto-1-hexanol was quickly injected. The solution changed from turbid to clear and transparent solution after a moment of reaction. It was naturally cooled to room temperature under nitrogen protection, and the precipitant toluene was added to the original reaction system solution. As the toluene increased, it can be seen that the clear solution gradually became turbid, indicating that the dispersibility of the quantum dots in the solution was weakened and gradually precipitated. The high-speed centrifuge was centrifuged at a speed of 7000 revolutions per minute for 3 minutes to precipitate the quantum dots, remove the precipitate and place it in a fume hood to dry, and grind it in a mortar after it is completely dried, and seal it for storage. Repeat the preparation and modification of large quantities of quantum dots according to the same ratio. Then, 5g of surface-modified quantum dots and 20g of EVOH polymer were weighed and put into 100g of polar solvent DMF, and heated at 50℃ for a long time to dissolve to form a uniform and stable liquid precursor gel. The prepared quantum dot polymer precursor solution was transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and was atomized into droplets by high-pressure nitrogen, and most of the polar solvent was instantly removed by a high-temperature thermal field (100℃). The whole process experienced the process of droplets becoming smaller and atomized, and the high-temperature thermal field was instantly dried. The equipment pressure was controlled to 75MPa and the fan frequency was 30Hz, forming a quantum dot microsphere polymer powder that was collected by the cyclone collector of the spray equipment. By setting the ALD coating equipment parameters and controlling the thickness of the Al2O3 deposition layer to 20nm, the quantum dot polymer powder was ALD coated, and the obtained ALD coated quantum dot polymer powder was recorded as sample 5.
[0080] Experimental Example 1
[0081] The samples 1 to 5 obtained above (respectively CdSe@ZnS (no polymer coating, no ALD coating), CdSe@ZnS (PMMA polymer coating, no ALD coating), CdSe@ZnS (PMMA polymer coating, ALD coating), CdSe@ZnS (PVDF polymer coating, ALD coating), CdSe@ZnS (EVOH polymer coating, ALD coating)) were mixed with prepolymer (2-hydroxy-3-phenoxypropyl acrylate), monomer (dicyclopentene Acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone) were mixed and stirred in a mass ratio of 2g:3g:5g:0.1g to obtain 5 kinds of glues, and then the coating machine was used to set the thickness to 50μm, and the 5 kinds of glues were respectively coated on the PET (polyethylene terephthalate) surface of the barrier diffusion film, both the upper and lower are barrier diffusion films, and cured for 3s by 365nm ultraviolet lamp to obtain 5 kinds of optical perovskite quantum dot films that can be used for optical performance testing and aging performance testing. The corresponding optical performance tests and corresponding aging data records were carried out on the obtained 5 kinds of quantum dot films, among which the optical performance test equipment model is Hera 01-VIS; the aging test equipment is an aging test box. The test results are shown in Table 1.
[0082] Table 1 Comparison of optical performance test and aging data of different samples
[0083]
[0084] Note: a The test conditions are: temperature 65°C, humidity 95%, 1000h;
[0085] b Test conditions: temperature 45°C, humidity 95%, light intensity 38W / m 2 (450nm), 1000h.
[0086] As shown in Table 1, the CdSe@ZnS (EVOH polymer coated, ALD coated) sample has the highest light conversion efficiency and the best wet-heat stability and light stability. This is sufficient to prove that the method of this application is crucial to improving the high stability of quantum dots and can be extended to a variety of polymer systems and quantum dot synthesis systems.
[0087] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for improving the stability of quantum dots, characterized in that: The steps include: (1) Obtaining core-shell quantum dot materials; (2) dissolving the core-shell quantum dot material, evacuating until there are no bubbles, heating, adding a quantum dot exchange ligand, cooling to room temperature, adding a precipitant, and centrifuging to obtain a polar quantum dot material; (3) heating and dissolving the mixture containing the polar quantum dot material and the polymer until a uniform and stable quantum dot polymer precursor gel is formed; (4) atomizing and instantaneously drying the quantum dot polymer precursor colloid in sequence to obtain quantum dot polymer microspheres; (5) Performing Al2O3 atomic layer deposition on the quantum dot polymer microspheres to obtain coated quantum dot polymer microspheres.
2. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (1), the core-shell quantum dot material includes at least one of CdSe@ZnS, CdSe@CdS, ZnSe@ZnS, and ZnSe@CdS.
3. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (2), the heating is carried out under an inert gas atmosphere; Preferably, in step (2), the temperature is increased to 100-350°C.
4. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (2), the quantum dot exchange ligand includes at least one of 6-mercapto-1-hexanol, 2-mercapto-3-butanol, 3-mercapto-1-propanol, and 2,3-dimercaptopropanol; Preferably, in step (2), the ratio of the core-shell quantum dot material to the quantum dot exchange ligand is 45-55 mg: 1-3 mL; Preferably, in step (2), the cooling is carried out under a nitrogen atmosphere.
5. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (2), the precipitant comprises toluene; Preferably, in step (2), the ratio of the core-shell quantum dot material to the precipitant is 45-55 mg: 5-13 mL; Preferably, in step (2), the centrifugal speed is 6000-8000 rpm; The centrifugation time is 1 to 5 minutes.
6. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (3), the polymer includes at least one of polymethyl methacrylate, polyvinylidene fluoride, polystyrene, polycarbonate, styrene-methyl methacrylate copolymer, polyethylene terephthalate, polypropylene, polyethylene, polyacrylonitrile, and acrylonitrile-styrene resin; Preferably, in step (3), the mixing mass ratio of the polar quantum dot material to the polymer is 1-3:20-35; Preferably, in step (3), the temperature of heating and dissolving is 40 to 60°C.
7. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (4), the atomization temperature is 60 to 100° C.; The atomizing gas pressure is 70-100 MPa; The fan frequency of the atomization is 20 to 50 Hz; Preferably, in step (4), the temperature of the instantaneous drying is 100-150°C.
8. A method for improving the stability of quantum dots according to claim 1, characterized in that: In step (5), the thickness of the Al2O3 atomic layer deposition is 10 to 100 nm.
9. A method for improving the stability of quantum dots according to claim 1, characterized in that: The method further comprises step (6): coating and photocuring a mixed glue solution containing the coated quantum dot polymer microspheres, prepolymer, monomer and photoinitiator in sequence to obtain a quantum dot film.
10. A method for improving the stability of quantum dots according to claim 9, characterized in that: The mixing mass ratio of the finished quantum dot polymer microspheres, prepolymer, monomer and photoinitiator is 1-3:1-4:2-5:0.1-0.3; Preferably, the coating has a thickness of 20 to 60 μm; Preferably, the energy of the light curing is 500 to 2500 mj / cm 2 .
Citation Information
Patent Citations
Perovskite quantum dot composite material and preparation method and application thereof
CN115717071A
Multi-layer coated quantum dot material and preparation method thereof
CN115852333A
Composite material as well as preparation method and application thereof
CN115991922A
Functional composite perovskite quantum dot material and preparation method and application thereof
CN116285945A
Lead group core-shell structure quantum dot and preparation method thereof
CN116814244A